Near-infrared light-mediated LA-UCNPs@SiO2-C/HA@mSiO2-DOX@NB nanocomposite for chemotherapy/PDT/PTT and imaging. Issue 41 (11th October 2017) - Chen, Yuhua; Zhang, Feng; Wang, Qian; Tong, Ruihan; Lin, Huiming; Qu, Fengyu
Abstract : Upon 980 nm light irradiation, multiple-emission can not only induce chemotherapy/PDT/PTT but also imaging. Abstract : Currently, incorporating multiple therapeutic functions into one nanoplatform is attracting increasing attention for the development of efficient anticancer agents. Here, a novel core–shell–shell nanoparticle, which was synthesized to integrate imaging and photodynamic therapy (PDT) with photothermal therapy (PTT) and chemotherapy for enhanced antitumor efficiency, consists of upconversion (UC) core (NaYF4 :Yb, Tm@NaYF4 ), Hypocrellin A (HA)/carbon dot (C-Dot) embodied silica sandwich shell, and mesoporous silica outer-shell. A photolabile o -nitrobenzyl derivative linker (NB linker) was prepared as the sensitive "gate" to encapsulate an anticancer drug (doxorubicin hydrochloride, DOX) in the mesopore. Upon 980 nm light irradiation, the UV-emission can induce the bond breaking of the NB linker as well as drug release. The visible emission can stimulate HA to generate singlet oxygen species (ROS); moreover the incorporated C-Dots also can absorb this light to evolve heat. In view of the excess expression of the lactobionic acid (LA) receptor on tumor cells, LA were grafted outside the nanocomposites to insure their specific targeting. The synergistic effect of NIR-triggered chemotherapy with PTT and PDT would be expected to reveal the enhanced cytotoxicity to cancer cells. And the novel UC and C/HA fluorescence also makes the nanocomposites a potential candidate for the imaging-guided multi-therapy.